Upaya Pembiasaan Membaca Al-Qur’an pada Karakter Siswa SMAIT Harum Karawang - Wiwin Siti Alawiyah; H. Amirudin; Iqbal Amar Muzaki (ISLAMIKA, 2022)
Islam needs to understand and have faith in all the commands of Allah SWT, and what is prohibited we should stay away from together in order to keep the faith of a Muslim to believe in every teaching, the guidelines given to the prophet Muhammad saw are to make Muslims understand how we study and believe it until there is no word of doubt for us to stick to and be guided by the holy book Al-Qur'an. As a believer we need to make sure to ourselves that if we always read every letter in the Qur'an then Allah will repay our kindness and will multiply our kindness, namely for those who always read it and memorize it at all times. Taking the method in this study is not forgotten from the title itself by doing a descriptive method by carrying out a descriptive qualitative approach the researcher can explain how the process of activities that occur in SMAI Harapan Ummah Karawang. The data collection techniques in this study were observation, interviews, and documentation of the activities of reading the Qur'an. Based on the results of the data obtained by researchers during the field and the results of interviews on the habit of reading the Qur'an, this program has given positive results on the level of students' ability in reading the Qur'an, Juzz 30 Memorization Activities, students understand more about the law of tajwid and makhraj in reading the Qur'an so that students can read properly and correctly.